The serendipitious city in South East Asia—urban archetypal design principles from the morphological ‘vernacular' - Jahn Kassim, Puteri Shireen; Kamaruddin, Kamariah; Abdul Latip, Nurul Syala; Mohd Nawawi, Norwina (Pisco Med Publishing, 2020)
‘Serendipitious’ has been defined as occurring or discovered by chance in a happy or beneficial way. “A serendipitous encounter” thus generally means one or a series of unexpected but pleasant encounters. A city, which is serendipitious, is a physical form, which has configuration and features which allows such encounters to happen. This paper highlights vernacular-based principles which are needed to counter the modernisation and urbanisation trends in South East Asia, throughout studying the typological and morphological character of ‘littoral maritime’ cities which grew in the 15th century onwards across littoral or coastal straits of maritime Asia represent pre-modern vernacular-rooted forms from which contain patterns that are urban, yet naturally-balanced with the environment. As these grew as a result of maritime trade, it is highly densed yet still reflect ecological features and conditions are still intact. The paper reconstructs some of these patterns and identify four central character as a result of their urban which resonate with ‘ecological themes’: 1) accretion qualities; 2) river-gravitation; 3) fractality and 4) centricity. The paper argues that although these patterns emerge from medieval times, these maritime cities constitute a ‘gentle’ and ecologically-sound approach to development which can unite the co-existence of urbanisation and nature. In such conditions, the tropical jungle exists side by side with densed urbanisation. The paper uses the reconstruction of the former (pre-colonial) morphologies in South East Asia to demonstrate the character of these centers, which are organic and informal evolvements having certain morphologies, configurations, architectural structures and their similarities and common principles in terms of urban patterns and principles are discussed. The pursuit of the optimal balance between ‘man’ and ‘nature’ must reflect in a city which consider living beings as both animal, vegetation and man, and which are, at present, in danger of critical depletion, and eventually extinction. Cases of built language, topography, ecology, landscape forms and urban configuration patterns and parameters across the region are presented and the paper argues that the rise of sustainability in city planning favors the compact and densed formal patterns which are reflective of these centers across the coastline of the straits historically and these constitutes principles that can sustain ecology, climatic balance yet an active cultural conduit of the place.